PTH-055 Efficacy of nasal bridles in preventing nasogastric tube displacement. The Royal Berkshire experience. (23rd September 2015) - Gupta, P K; Fitchett, J; Simmons, J D; DeSilva, A N
Abstract : Introduction: Rates of accidental removal of nasogastric feeding tubes (NGT) within hospital can reach up to 60% which exposes patients to risk from repeat procedures as well as consuming resources. Nasal bridles are not routinely used in the UK despite demonstrating a reduction in NGT removal rates, reducing the occurrence of unnecessary percutaneous gastrostomy (PEG) placements and increasing nutrition delivery. At the Royal Berkshire Hospital patients are deemed suitable for bridle placement if three or more NGT have been removed unintentionally, there is no history of nasal trauma and not so confused as to risk causing themselves nasal septal injury. All patients are assessed by a clinical nurse specialist. It is Trust policy to confirm all NGT placements with a chest x-ray. We audited our practice to assess whether bridles are effective and safe. Methods: Database records for all patients referred for NG bridles between June 2007 and September 2009 were reviewed. Where additional information was required, case notes were obtained. Radiology exposure was also assessed. Results: fifty-one patients were referred for bridle placement during the 27-month audit period. Median age was 72 years (range 36–90). Cerebrovascular accident was the most common reason for referral (82%). All patients had had at least 3 NGT placed prior to referral (median 3 range 3–8). 38 of the 51 patients (74.5%) had bridles attached using 39 devices in total. One patient required bridle replacement and only one experienced significant nasal trauma. The reasons for not placing a bridle included; 2 were too unwell, 6 were already eating, 3 refused and 2 were too difficult to place. Of these 5 went straight to PEG feeding. The 38 bridle patients received 308 days of NGT feeding (median 7 range 1–32). Of these only two required long-term PEG feeding and 21 were able to have their bridles removed as they were no longer required. Fifteen patients with bridles died for reasons unrelated to their bridle. An additional 147 chest x-rays had been used prior to referral while only one additional x-ray was required to confirm NGT position after bridle placement. Conclusion: Bridle fixation reduces the number of NGT re-insertions, inappropriate PEG tubes and helps to prevent delay of nutrition restoration. They also reduce repeated radiation exposure from recurrent x-rays and overall hospital costs. Bridles have a very low incidence of complication and help reduce unnecessary PEG insertions in high-risk groups if patients are assessed carefully by trained staff.